Association Among Dietary Supplement Use, Nutrient Intake, and Mortality Among U.S. Adults: A Cohort Study - Chen, Fan; Du, Mengxi; Blumberg, Jeffrey B; Ho Chui, Kenneth Kwan; Ruan, Mengyuan; Rogers, Gail; Shan, Zhilei; Zeng, Luxian; Zhang, Fang Fang (Annals of internal medicine, 2019)
The health benefits and risks of dietary supplement use are controversial. To evaluate the association among dietary supplement use, levels of nutrient intake from foods and supplements, and mortality among U.S. adults. Prospective cohort study. NHANES (National Health and Nutrition Examination Survey) data from 1999 to 2010, linked to National Death Index mortality data. 30 899 U.S. adults aged 20 years or older who answered questions on dietary supplement use. Dietary supplement use in the previous 30 days and nutrient intake from foods and supplements. Outcomes included mortality from all causes, cardiovascular disease (CVD), and cancer. During a median follow-up of 6.1 years, 3613 deaths occurred, including 945 CVD deaths and 805 cancer deaths. Ever-use of dietary supplements was not associated with mortality outcomes. Adequate intake (at or above the Estimated Average Requirement or the Adequate Intake level) of vitamin A, vitamin K, magnesium, zinc, and copper was associated with reduced all-cause or CVD mortality, but the associations were restricted to nutrient intake from foods. Excess intake of calcium was associated with increased risk for cancer death (above vs. at or below the Tolerable Upper Intake Level: multivariable-adjusted rate ratio, 1.62 [95% CI, 1.07 to 2.45]; multivariable-adjusted rate difference, 1.7 [CI, -0.1 to 3.5] deaths per 1000 person-years), and the association seemed to be related to calcium intake from supplements (≥1000 mg/d vs. no use: multivariable-adjusted rate ratio, 1.53 [CI, 1.04 to 2.25]; multivariable-adjusted rate difference, 1.5 [CI, -0.1 to 3.1] deaths per 1000 person-years) rather than foods. Results from observational data may be affected by residual confounding. Reporting of dietary supplement use is subject to recall bias. Use of dietary supplements is not associated with mortality benefits among U.S. adults. National Institutes of Health.